(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Our investigation aimed to formulate a bilayer matrix tablet that includes Vildagliptin as a component for prolonged release and acarbose for immediate release. Treatment with these medications provides a high standard of living for individuals afflicted with type II diabetes mellitus. This medicine offers several key benefits, including its precise targeting of specific actions, exceptional safety, and outstanding effectiveness. Acarbose was immediately formulated with super disintegrants, specifically sodium starch glycolate (SSG) and croscarmellose sodium (CCS). The tablet was then compressed via direct compression. Sustained release layer of vildagliptin was prepared utilizing HPMCK100 as release retarding polymers. The wet granulation technique was employed, and PVP K30 in IPA solution (10%) was used as a granulating agent. The bilayer tablet underwent evaluation for several characteristics, including hardness, friability, weight variation, percentage of medication content, percentage of medication release study, and disintegration time of IR layer. An optimization process was used to refine a formulation, resulting in a formulation that contains 12 mg of CCS and 32 mg of HPMC K100M. Optimized formulation shows 98.3±1.05% immediate release and 34.54±1.54%, 69.32±1.60% and 96.75±2.13% drug release at 1, 4 and 8 hours, respectively. Our study revealed that bilayer tablets including Vildagliptin and Acarbose might be a superior alternative to standard dosage forms.